Plants Potential of Green and Open Space Planning (RTH) to Mitigate CO2 Gas Emission in Ambon - Frenly Marvi Selano; Ris Hadi Purwanto; Probo Santoso (Biotropika: Journal of Tropical Biology, 2021)
The urbanization rate may give an adverse effect on a city. For example, it accrues the number of urban dwellers and induces the exploitation of land resources with a quick conversion rate, which leads to the degradation of the quality of the environment. This condition is exacerbated by deescalated green and open spaces (RTH) as a CO2 absorber. CO2 emissions in urban regions can be mitigated by exerting trees, which have a pivotal role in carbon uptake. This research imparts an analysis of plant species that are potential for absorbing carbon and storing biomass in green and open spaces in Ambon. The research method is quantitative by estimating biomass and carbon uptake of trees. Results indicate that trembesi (Samanea saman), linggua (Pterocarpus indicus), mahoni (Swietenia macrophylla), bintanggur (Calophyllum inophyllum), and kerai payung (Filicium decipiens) are typical trees planted in Ambon. The highest CO2 uptake capacity (B = 110.95 tons/ha, CO2 = 191.38 tons/ha) is identified in Trembesi (Samanea Saman), linggua (Pterocarpus indicus), the second-highest with a B = 61.66 tons/ha and CO2 = 106.36 tons/ha, and Akasia (Acacia mangium), the third-highest with a B = 25.24 tons/ha and CO2 = 41.69 tons/ha